The CSF-Contacting Nucleus Receives Anatomical Inputs From the Cerebral Cortex: A Combination of Retrograde Tracing and 3D Reconstruction Study in Rat - Song, Si-Yuan; Zhai, Xiao-Meng; Dai, Jia-Hao; Lu, Lei-Lei; Shan, Cheng-Jing; Hong, Jia; Cao, Jun-Li; Zhang, Li-Cai (Frontiers in Neuroanatomy, 2020)
Objective This study aimed to investigate the direct monosynaptic projections from cortical functional regions to the CSF-contacting nucleus for understanding the functions of the CSF-contacting nucleus. Methods The Sprague–Dawley rats received cholera toxin B subunit (CB) injections into the CSF-contacting nucleus. After 7-10 days of survival time, the rats were perfused, and the whole brain and spinal cord were sliced under a freezing microtome at 40 μm. All sections were treated with the CB immunofluorescence reaction. The retrogradely labelled neurons in different cortical areas were revealed under a confocal microscope. The distribution features were further illustrated under 3D reconstruction. Results The retrogradely labelled neurons were identified in the olfactory, orbital, cingulate, insula, retrosplenial, somatosensory, motor, visual, auditory, association, rhinal, and parietal cortical areas. A total of 12 functional areas and 34 functional sub-regions showed projections to the CSF-contacting nucleus in different cell intensities. Conclusion According to the connectivity patterns, we conclude that the CSF-contacting nucleus participates in cognition, emotion, pain, and visceral activity, etc. The present study firstly reveals the cerebral cortex→CSF-contacting nucleus connections, which implies the multiple functions of this special nucleus in neural and body fluids regulations.